Assessment of dietary sodium intake using a food frequency questionnaire and 24‐hour urinary sodium excretion: a systematic literature review. Issue 12 (8th December 2017) - McLean, Rachael M.; Farmer, Victoria L.; Nettleton, Alice; Cameron, Claire M.; Cook, Nancy R.; Campbell, Norman R. C.; ,
Abstract : Food frequency questionnaires (FFQs) are often used to assess dietary sodium intake, although 24‐hour urinary excretion is the most accurate measure of intake. The authors conducted a systematic review to investigate whether FFQs are a reliable and valid way of measuring usual dietary sodium intake. Results from 18 studies are described in this review, including 16 validation studies. The methods of study design and analysis varied widely with respect to FFQ instrument, number of 24‐hour urine collections collected per participant, methods used to assess completeness of urine collections, and statistical analysis. Overall, there was poor agreement between estimates from FFQ and 24‐hour urine. The authors suggest a framework for validation and reporting based on a consensus statement (2004), and recommend that all FFQs used to estimate dietary sodium intake undergo validation against multiple 24‐hour urine collections.